(untitled) (Journal of Applied Membrane Science & Technology, 2021)
Pseudo-emulsion based hollow fiber strip dispersion (PEHFSD) is a promising alternative technique due to its stability, simplicity and cost of operation. This is an efficient process due to its high surface area for extraction as well as stripping, and low energy consumption for creating the pseudo-emulsion and for the separation of phases. This technique takes the combine advantages of emulsion liquid membrane and overcomes the sufferings of membrane stability in the supported liquid membrane systems. Present work includes extraction of neodymium (III) (Nd) by using TODGA and HNO3 as the extractant cum strippant in PEHFSD technique. A model is developed to study the transport of Nd under different hydrodynamic and chemical conditions that includes organic ratio (A/O) in dispersion, effect of speed of impeller on drop size formation, effect of feed acidity, effect of carrier concentration, effect of feed flow rate. A code is written to solve the model equations numerically to predict the concentration of the feed reservoir with time. Experiments are conducted to obtain the best optimum extraction conditions. Results obtained from the numerical simulations are validated with the experimental data and found a good agreement between them.